Linking openness to cognitive ability in older adulthood: The role of activity diversity. (2nd July 2020) - Jackson, Joshua J.; Hill, Patrick L.; Payne, Brennan R.; Parisi, Jeanine M.; Stine-Morrow, Elizabeth A. L.
Abstract: Relatively few studies have examined the reasons older individuals participate in activities that may benefit cognition with aging. Personality traits, particularly, openness to experience, are likely to influence how activities are selected. Openness to experience has also reliably shown to relate to cognitive and intellectual capacities. The current study tested whether diversity in activity helped to explain the overlap between openness to experience and cognitive functioning in an older adult sample (n = 476, mean age: 72.5 years). Results suggest that openness is a better predictor of activity diversity than of time spent engaged in activities or time spent in cognitively challenging activities. Further, activity diversity explained significant variance in the relationship between openness and cognitive ability for most constructs examined. This relationship did not vary with age, but differed as a function of education level, such that participating in a more diverse array of activities was most beneficial for those with less formal education. These results suggest that engagement with a diverse behavioral repertoire in late life may compensate for lack of early life resources.